DEVELOPMENT OF INTERACTIVE MULTIMEDIA ON NUMBER THEORY BASED ON METACOGNITIVE SKILLS - Astuti, Wiwin; Izzati, Lihar Raudina; Suyatman, Suyatman (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research develops interactive multimedia based on metacognitive skills with the Lectora Inspire application. The multimedia presented is in the form of material, videos and quizzes that support the number theory course. This multimedia is also equipped with instructions and directions to improve metacognitive abilities in the form of planning, monitoring and evaluating at each stage of the learning process. The development model used in this research is DDD-E. The validity of interactive multimedia was carried out by 3 media experts and 3 material experts. The practicality test was carried out by 3 Tadris Mathematics lecturers and 30 Tadris Mathematics students at UIN Raden Mas Said Surakarta. The results of interactive multimedia validation by material experts were 3.66 (very good) and the results of interactive multimedia validation by media experts were 3.75 (good). The results of the usage test by Tadris Mathematics lecturers produced a score of 3.69 (very good) and by Tadris Mathematics students 3.58 (very good). This shows that the interactive multimedia developed is suitable for use.